604 Intravenous CMP-001, a CpG-A Toll-like receptor 9 (TLR9) agonist delivered via a virus-like particle, causes tumor regression in syngeneic Hepa1–6 mouse models of hepatocellular carcinoma. (10th December 2020) - Morris, Aaron; Walters, Evan; Akache, Bassel; McCluskie, Michael; Krieg, Arthur
Abstract : Background: Therapeutic options are limited for patients with liver metastases and hepatocellular carcinoma (HCC). Intratumoral and subcutaneous injections of CMP-001, a CpG-A TLR9 agonist packaged within a virus-like particle, have shown evidence of antitumor activity in patients with melanoma refractory to PD-1 blockade. In mice, CMP-001 intravenous distributes primarily to the liver, while CMP-001 subcutaneous is found mostly in local tissues and draining lymph nodes. The antitumor activity of CMP-001 intravenous and subcutaneous were compared with PD-1 blockade or sorafenib in two Hepa1-6 orthotopic mouse models of HCC. Methods: Groups of 10–15 C57BL/6J mice were orthotopically implanted with syngeneic murine hepatoma cells using two different models. Model 1 used 1.5 x 10 6 Hepa1-6 cells injected into the spleen following a partial hepatectomy; Model 2 used 1 x 10 6 Hepa1-6-Luc cells injected into the upper left lobe of intact liver. Treatment was initiated 3–7 days later with either CMP-001 intravenous or subcutaneous Q4-5Dx3-4 doses, PD-1 blocking antibody intraperitoneal Q3-4Dx2 (Bio X Cell clone RPM1-14), or sorafenib QD oral. Antitumor activity was assessed by tumor imaging, liver weight, and/or survival. Results: CMP-001 was compared with PD-1 blocking antibody therapy in Model 1, the more aggressive model. All animals were sacrificed at day 15 due to institutional welfare requirements. Tumor growth inhibition (TGI) was assessed by comparison of liver weight to body weight ratios, which relative to untreated control mice showed that CMP-001 intravenous achieved 85% mean TGI compared with 63% mean TGI for CMP-001 subcutaneous and 15% mean TGI for PD-1 blocking antibody intraperitoneal (table 1 ). CMP-001 intravenous was compared to sorafenib oral in Model 2, which utilized an engineered Hepa1-6 cell line that expresses luciferase to enable noninvasive monitoring of liver tumor growth. CMP-001 intravenous was active, with a 67% mean TGI, and survival that was comparable to sorafenib (table 2 ; figure 1 ). Conclusions: In orthotopic mouse models of HCC, the antitumor activity of CMP-001 intravenous was greater than PD-1 blockade and comparable to sorafenib. CMP-001 intravenous was more active than CMP-001 subcutaneous in this model, which we hypothesize is due to increased liver exposure with intravenous infusion. Antitumor activity of CMP-001 monotherapy may be increased by combining it with standard of care or other therapies, as observed relative to historical benchmarks in ongoing CMP-001 clinical trials in patients with melanoma. CMP-001 intravenous may be a promising treatment option for patients with primary or metastatic liver cancers. Acknowledgements: This work was supported by Checkmate Pharmaceuticals. Studies were performed at Oncodesign Biotechnology (Dijon, France) and Crown Bioscience UK Ltd (Osgathorpe, UK) and National Research Council Canada (Ottawa, Ontario, Canada) and funded by Checkmate Pharmaceuticals. Ethics Approval: At Oncodesign Biotechnology, animal housing and experimental procedures were conducted according to French and European Regulations and the National Research Council Guide for the Care and Use of Laboratory Animals. The animal facility is authorized by the French authorities (Dijon: Agreement B21231011EA). The study and all animal procedures were approved by the Institutional Animal Care and Use Committee of Oncodesign (Oncomet) approved by French authorities (CNREEA agreement number 91). At Crown Bioscience, animal care and experimental procedures were compliant with the UK Animals Scientific Procedures Act 1986 (ASPA) in line with Directive 2010/63/EU of the European Parliament and the Council of 22 September 2010 on the protection of animals used for scientific purposes. At National Research Council Canada, animals were maintained in accordance with the guidelines of the Canadian Council on Animal Care, and all experimental procedures were performed in accordance with regulations and guidelines reviewed and approved by the NRC Human Health Therapeutics Ottawa Animal Care Committee.